Characteristics of disease in children at earthquake evacuation camps in West Pasaman Regency and Pasaman Regency in 2022 - Arsyad As Siddiqi Abdurrahman; Ihsan Indra (E3S Web of Conferences)
Extraordinary occurrences of infectious diseases may occur when earthquakes result in large population movements to unplanned and overcrowded shelters with limited access to safe food and water sources. An earthquake with a magnitude 6.1 shook West Pasaman Regency, West Sumatra Province, on Friday (2/25/2022). Many disaster victims sleep in open areas so that they are exposed to dust, heat, and poor hygiene. Method: A descriptive study conducted retrospectively from pediatric patient data who came to health facility tents in refugee camps in West Pasaman and Pasaman Regency, collected from February 2022 to April 2022. The total number of visits was 247 pediatric patients. Air-borne disease suffered by 78.5%, followed by food and water-borne diseases (13%) and vector related disease (2.8%). Acute respiratory infection is the most common disease suffered by 184 cases (74.4%) followed by acute diarrhea (5.2%). There were also 8 cases of measles that were potential for outbreaks infectious diseases. Airborne disease is the most common disease suffered by refugees, followed by food-water borne and vector related disease. The availability of complete data on diseases can facilitate the implementation of optimal health services and help prevent the occurrence of outbreaks among disaster victims.